Civil Law Analysis of Application for Change of Name at Rembang District Court - Pungki, Nanda Ayu; Rizda Sabti Yulnita; Dian Latifiani (Universitas Muhammadiyah Surakarta, 2022)
The State of Indonesia is a state of law which is regulated in Article 1 paragraph 3 of the 1945 Constitution. One of the implementations of legal products is the settlement of disputes or problems that are contrary to the law by courts. In this study, we want to examine the problem of the application for a name change in the District Court according to the facts that occurred in Rembang. This study uses a qualitative approach which makes observations directly to the field to find the truth value related to the research. The results of the study found that along with the times, the application for change of name was very much found in people’s lives. But the fact is that many people are still confused about the name change application process. The purpose of this study is to find the problems in the application case encountered when wanting to change the name and provide information about the procedures related to submitting a name change application at Rembang District Court based on court principles to achieve certainty, benefit, and legal justice